Education Financing Strategies in Improving the Quality of Islamic Education Institutions - Susisofianti, Susisofianti; Karim, Hamdi Abdul (STIT Ahlussunnah Bukittinggi, 2025)
Improving the quality of Islamic educational institutions is highly dependent on effective, efficient, and sustainable financing strategies. This study aims to analyze various financing strategies that can be applied to improve the quality of Islamic education. Through a literature review, this article identifies several key strategies, including: the integration of information technology in financial management, diversification of funding sources, economic empowerment of the community through pesantren business units, and optimization of Islamic philanthropic funds such as zakat, infaq, sadaqah, and waqf. Additionally, participatory budgeting, regular evaluation, and strict oversight are also crucial pillars in an accountable and transparent financing system. This study shows that effective financing strategies have a positive impact on improving educators' competencies, providing adequate facilities and infrastructure, and increasing community participation. However, challenges remain, such as limited resources, resistance to digitalization, and weak managerial capacity. Therefore, synergy between the government, community, and educational institutions is needed to strengthen financing policies and governance. The results of this study provide recommendations for strengthening data-based financial systems, professionalizing fund management, and involving all stakeholders to achieve excellent, independent, and sustainable Islamic education.